Cigar Warning Noticing and Demographic and Usage Correlates: Analysis from the United States Population Assessment of Tobacco and Health Study, Wave 5 - Gratale, Stefanie K.; Teotia, Arjun; Chen-Sankey, Julia; Ganz, Ollie; Delnevo, Cristine D.; Strasser, Andrew A.; Wackowski, Olivia A. (International journal of environmental research and public health, 2022)
Although cigars pose health risks similar to cigarettes, their packaging/marketing is not subject to commensurate regulation in the US. In a 2000 agreement with the Federal Trade Commission, seven major manufacturers agreed to use some form of cigar warning. In 2016, the Food and Drug Administration passed a rule requiring larger standardized warnings, but the requirement was successfully challenged in court. Here, we examined U.S. population-level trends in noticing existing cigarillo, traditional and filtered cigar warnings. We analyzed Wave 5 Population Assessment of Tobacco and Health adult data to assess prevalence of past-30 day warning noticing and associations with socio-demographic and tobacco use variables. Noticing was higher among current users of cigarillos (27%), filtered (34%) and traditional cigars (21%), than non-users (8% for each product, p < 0.0001), and among every-day vs. some-day users, established vs. experimental users, and past-30 day users vs. those without past-30 day use. Results varied by product, but generally indicated lower noticing among non-Hispanic Whites and dual cigarette users, but higher noticing among those purchasing cigars by the box/pack (vs. not purchasing for themselves). Low overall noticing but higher prevalence among frequent users underscores a need for a stronger, uniform cigar warning label policy in the US.